Teamwork in Patient Care Delivery: Assessing the Perceptions of Government Medical Officers - Rehin. K.R and P.T. Raveendran (Asian J. Management, 2015)
The very definition of organization as a group of people working together emphasizes the importance of teamwork in the accomplishment of organizational goals. Health Care is a domain where teamwork cannot be overlooked under any circumstance with the doctors, patients, nurses, support staff as well as bystanders having their own respective roles. Effective care delivery can be ensured only if all the stakeholders work in tandem with each other. Hence, this paper examines the effectiveness of teamwork at government hospitals in Kerala as perceived by the doctors working there. Exploratory factor analysis of responses from 240 government doctors across Kerala indicated that ‘joint effort in patient care’ was the sole determinant of effective teamwork at government hospitals. Multiple regression analysis further revealed that most of the doctors unanimously felt that effective teamwork was missing at government hospitals across Kerala, which requires immediate attention on part of the authorities, considering the significance of teamwork in effective patient care delivery.